Methods of Teaching Students to Grammatical Analysis in Mother Language and Reading Literacy Lessons - Sharofova Nilufar Ilhom Qizi; Azimova Dilfuza Usmanovna (Genius Journals, 2023)
Grammatical analysis has a great role in increasing the effectiveness of mother tongue and reading literacy classes, and in applying the theoretical knowledge acquired by students in the practical process
Keywords: Literacy Lessons; education system; grammar